ANALYZING SANTRI NEEDS FOR ENGLISH DEBATE AS A STRATEGY TO SUPPORT GLOBAL COMMUNICATION READINESS - Novi Dwi Yuliani; Lailatun Najmiah; Muhammad Rifqy Rujani; Nurul Hidayah Ramadani (Universitas Muhammadiyah Makassar, 2025)
This study investigates the specific needs of beginner-level students engaged in English debate activities within the Language Area program at an Islamic boarding school in South Kalimantan, Indonesia. Recognizing the increasing role of debate as a pedagogical strategy in English as a Foreign Language (EFL) contexts, the research aims to explore linguistic, emotional, and cultural needs that are often overlooked in generic debate materials. A qualitative descriptive design was employed, using open-ended questionnaires distributed to 60 English Club members and semi-structured interviews were done to one debate coach, and one student as a delegation. Thematic analysis revealed that students not only seek to improve their speaking skills, but also desire confidence, logical argumentation, and culturally relevant content. Participants emphasized the importance of structured guidance, beginner-friendly materials, and emotional support to overcome anxiety and build motivation. The findings confirm the value of debate in fostering speaking fluency, critical thinking, and collaboration, particularly when activities are adapted to the pesantren context. The study highlights a strong demand for a tailored debate handbook that aligns with students’ religious, social, and educational environments. This research contributes to the growing field of learner-cantered EFL materials design and offers practical implications for integrating culturally sensitive debate instruction in Islamic boarding schools.